The difference of c and 13 is less than -19.
if you want the inequality, c - 13 < -19
if you want the inequality simplified, c < -6
step-by-step explanation: first, on the right side you subtract (90-114) - (66). the answer will be -90. then, you set the equation up as s+24=-90. to get s by itself, subtract 24 from both sides. it should look like this s+24-(24)=-90-(24). once you know that -90-24=-114, your new equation will be s=-114. therefore, the value of s is -114. if you need reassurance, you can add 24 to -114, which gives you -90.